Workload Analysis of Doctors at Puskesmas Using Workload Indicators of Staffing Need in Denpasar - Anak Agung Ngurah Gede Dharmayuda; Luh Putu Lila Wulandari; Dewa Nyoman Wirawan (Universitas Udayana, 2015)
Background and purpose: Ratio of health staff instead of workload have been used to determine quota of staff at primary health centers. There is no study assessing workload of functional medical doctors (general practitioners) at primary health centers in Bali. The objectives of this study were to describe functional medical doctors workload, the number and distribution which is needed in primary health centers in Denpasar. Methods: Descriptive cross-sectional study was conducted among functional medical doctors at 11 primary health centers across Denpasar. Data were collected by interview and participatory observation to the study participants. Data was analyzed using WISN English Version 1.1.132.0 software. Results: Among 34 study participants, majority were female (73.5%), aged 35-44 years (61.8%), working as a government employee (97.1%), with tenure of 6-10 years (55.9%) and almost all of them (95.6%) had additional duties besides providing medical care to patients. Results indicated that workload of functional medical doctors at primary health centers was high with WISN ratio 0.5-0.9 compared to the ideal ratio=1. Based on workload analysis, shortages of functional medical doctors was found in all primary health centers in Denpasar. Conclusion: When using the ratio of functional medical doctors per population, the number was sufficient. However, when using workload analysis indicated shortage.